Analyzing two platforms: NET and Java for deveroping a search engine - Bhuiyan, Shoman (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2008.